Effectiveness of Azadirachta Indica (Neem) Plant Extract Compared with Albendazole on the Vitality of Hydatid Cyst Protoscolices (In Vitro) - Jari, Sawsan Darweesh (Technium BioChemMed, 2025)
The cestode worm Echinococcus granulosus larval stage parasitically infects humans and animals' livers and lungs, causing cystic echinococcosis. Surgery with scolicidal agents to inactivate live protoscolices is the main treatment for cystic echinococcosis (CE). An extract of neem tree leaves was chosen to treat this parasite that causes this disease, and its effects were laboratory tested on the vitality of the primary fungi, which is infective to humans, taken from the livers of infected sheep in the holy governorate of Karbala. This study used four concentrations of alcoholic neem tree leaf extract (1.250, 2.500, 5.000, and 10.000) ppm to count protoscolices in 5microliter volumes before and after treatment and compare them to albendazole. All concentrations of Neem leaves extract were effective, but 10,000 ppm was the most effective, as the percentage of mortality reached 100% after 30 minutes. The lower concentration of 1,250 ppm caused 90.62 % after 240 minutes. The above shows that Neem plant extracts inhibited protoscolices growth in all treatments. Due to its wide range of chemicals and biologically active compounds, which affect parasite cell mitochondrial membranes and cause apoptosis, many scholars call it the tree of the future.